The impact of pricing strategies on time-on-market under various economic conditions - C. M. Hui, Eddie; Yu, Ka Hung (International Journal of Strategic Property Management, 2012)
This study examines how price adjustments in a flat’s marketing phase, along with various housing attributes, influence its time-on-market (TOM). A Cox survival model is used for the analysis of two separate periods, one of economic downturns (2003) and one of economic recovery (2004–2006), in Hong Kong. Factors such as price adjustments, sale price, numerous housing attributes, general property price trend, and changes in unemployment rate have significant impacts on TOM, with their respective impacts changing over time. Specifically, the effectiveness of raising list prices before transactions, in optimizing sellers’ returns and TOM, depends on economic conditions as well as on the market expectations regarding future property prices. Directions on future studies are then discussed. First Publish Online: 12 Apr 2012